The persistent problem of drowning - A difficult diagnosis with inconclusive tests. (August 2019) - Stephenson, Lilli; Van den Heuvel, Corinna; Byard, Roger W.
Abstract: Although the diagnosis of drowning may appear straightforward the reality is that it is sometimes one of the most difficult in forensic pathology. To begin with, there is no universal agreement on what constitutes drowning with some definitions using the term in the absence of a lethal outcome. Next are the significant problems that arise in finding immersed bodies and in assessing the death scene. Prolonged post mortem intervals are associated with artefactual modifications of the body from putrefaction and post mortem animal predation. Both of these may create and disguise injuries. The absence of pathognomonic pathological features at autopsy and the presence of potentially life threatening underlying organic illnesses complicate determination of both the cause and manner of death. There may even be no autopsy findings to indicate that immersion had occurred. Finally, the unreliability of laboratory tests with significant overlap with control cases where death had no association with immersion presents further problems. Thus lethal drowning remains a complex event that requires the use of a wide variety of information sources, not just data gleaned from the dissection table.